INCARCERATED GRAVID UTERUS IN VENTRAL HERNIA - Qadir, Sara; Malik, Sajid; Iftikhar, Nimra (Journal of Ayub Medical College Abbottabad, 2023)
Incarcerated gravid uterus for in ventral hernia is an extremely rare obstetrical and surgical problem which contributes to pregnancy related complications. We searched for literature to identify aetiology, presentation, complications, and management options for incarcerated gravid uterus, and are presenting this case with literature review. This extremely rare case report, first ever from Pakistan, of an incisional hernia containing gravid uterus as its contents and is bulging out of abdominal cavity. She presented at 27 weeks with ulceration of ventral hernia skin. She was offered a conservative treatment keeping in view maternal and foetal monitoring until term. A full-term elective lower segment caesarean section (LSCS) followed by open mesh repair was done. A successful outcome was observed. There are limited treatment options for uterine incarceration into ventral hernia, but definitive diagnosis allows procedures to treat and to reduce severe maternal and foetal complications. There is no consensus over the management of this rare condition. A tailor approach should be opted in each case. If uncomplicated, a conservative approach until term followed by delivery or LSCS and hernioplasty is a good option.